2020
DOI: 10.1186/s12885-020-07688-2
|View full text |Cite
|
Sign up to set email alerts
|

A genomic-clinicopathologic nomogram for predicting overall survival of hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is a common digestive tumor with great heterogeneity and different overall survival (OS) time, causing stern problems for selecting optimal treatment. Here we aim to establish a nomogram to predict the OS in HCC patients. Methods International Cancer Genome Consortium (ICGC) database was searched for the target information in our study. Lasso regression, univariate and multivariate cox analysis were applied during the analysis process. And a nomogram integrating model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The above results were consistent with many previous researches [43][44][45]. Besides, our results also demonstrated that age and gender were also associated with the histopathologic grade and MVI of HCC, which corresponded to some previous findings that the age and gender also served as independent risk factors and then were incorporated into the nomogram-based predictors [46][47][48]. Importantly, this study suggested that the integration of clinical indicators and radiomics resulted in fascinating diagnostic power for assessing the tumor grade and MVI (AUC > 0.900).…”
Section: Notesupporting
confidence: 92%
“…The above results were consistent with many previous researches [43][44][45]. Besides, our results also demonstrated that age and gender were also associated with the histopathologic grade and MVI of HCC, which corresponded to some previous findings that the age and gender also served as independent risk factors and then were incorporated into the nomogram-based predictors [46][47][48]. Importantly, this study suggested that the integration of clinical indicators and radiomics resulted in fascinating diagnostic power for assessing the tumor grade and MVI (AUC > 0.900).…”
Section: Notesupporting
confidence: 92%
“…We collected literature on hepatocellular carcinoma, 18 , 19 , 20 extracted the genes they used to construct predictive models and performed survival curve and ROC curve analysis to compare the predictive power of our constructed models.…”
Section: Methodsmentioning
confidence: 99%
“…Nomogram is considered a widely used predictive model for evaluating the prognosis of cancer patients [12][13][14]. In this study, we aim to identify the prognostic factors of elderly patients with HCC and construct a new prognostic model for predicting their OS, which would facilitate the provision of therapy suggestions and assist clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%